Internal exposure of firefighting instructors to polycyclic aromatic hydrocarbons (PAH) during live fire training. (1st October 2020) - Rossbach, Bernd; Wollschläger, Daniel; Letzel, Stephan; Gottschalk, Wolfgang; Muttray, Axel
Highlights: Live fire training leads to additional uptake of PAH inspite of respirator use. Urinary PAH metabolites as powerful tool to assess exposure including dermal uptake. Metabolite excretion kinetics suggest accumulative effects after repeated exposure. Results on excretion kinetics help to schedule biomonitoring studies. Abstract: Firefighting instructors in live fire training are inevitably exposed to emissions containing, carcinogenic PAH. The study investigated PAH uptake in a group of firefighting instructors during short-term exposure in live fire training by urinary biomonitoring. Six firefighting instructors (non-smokers) completed five 2 h-training sessions each in a carbonaceous-fired simulation unit using self-containing breathing apparatuses (SCBA). Complying with a minimum time interval of six days between the individual training sessions, the participants provided urine samples before and immediately after, as well as 1, 3, 6, 9, 11, and 18 h after each training session. Samples were analyzed for 10 mono-hydroxylated metabolites of the PAH naphthalene, fluorene, phenanthrene and pyrene using gas chromatography/tandem mass spectrometry. A significant effect of the training sessions on the time course of internal exposure was found (p < 0.0001). The concentration of all parameters clearly increased at the latest 3 h after end of training. After peaking, the concentrations dropped with half-lives between 3.5 and 9.3 h but did not reach the initial levels within 18 h again. Compared to pre-training levels, the increase in metabolite excretion was between 546–933 %. During peak excretion reference values for hydroxynaphthalene (35 μg/L, sum of 1- and 2-isomer) and 1-hydroxypyrene (0.30 μg/L) were exceeded in 64 % (maximum: 381.3 μg/L) and 73 % of the samples (maximum: 1.88 μg/g crea.), respectively. Live fire training is associated with an additional uptake of PAH. Due to the consequent use of SCBA, dermal absorption is assumed as major exposure route. Further measures to reduce PAH exposure should be considered, in particular since higher internal loads caused by accumulation effects are to be expected with daily or more frequent training.